Cegah Stunting dengan Sosialisasi Pentingnya Kesehatan dan Gizi di Desa Prapat Tunggal - Muhammad Kamil Purba; Muhammad Rasyid Raihan; Al Azhari Husaini; Istiq Bedria; Lila Yani; Luthfiyyah Dorrotul Hikmah; Maharani Maharani; Salsabilla Gusliantyna; Yonna Indrawan; Nola Martasela (jurnal ABDIMAS Indonesia, 2023)
This socialization aims to provide knowledge to the community about what stunting is and the dangers of stunting on the growth and development of their children and provide teaching on how to prevent stunting from occurring and provide understanding to residents that there are several processed foods and the main ingredients come from local food sources that they can use. exercise to prevent stunting and malnutrition affecting children or their relatives. We invite residents to understand more about what stunting and malnutrition are so that their children or relatives do not get the disease and also provide recommendations for appropriate foods to prevent stunting and malnutrition and also solutions for parents whose children are already pregnant. affected by stunting and malnutrition by providing information on where this child is taken for treatment and also how to treat stunting and malnutrition.